Breaking bread, breaking beats : churches and hip-hop : a basic guide to key issues (Fortress Press, 2014)
In this innovative project, ten individuals write as one voice to illuminate the ways that Hip-Hop and the Black Church agree, disagree, and inform each other on key topics. This book grows out of the popular religion and Hip-Hop course offered at Rice University by Dr. Anthony Pinn and Bernard 'Bun B' Freeman. Like the course, the book offers engaging insights into one of the most important musical genres and reflects on its broad cultural impact.